2017
DOI: 10.1159/000464250
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ERBB Family of Ligands and Receptors in Gastric Cancer

Abstract: Objective: Gastric cancer (GC) is the second most common cancer and the third leading cause of cancer-related death in Korea. Alterations in the ERBB (homology to the erythroblastoma viral gene product, v-erbB) receptor family and ERBB-related signaling pathways are frequently observed in GC. However, the roles of the ERBB receptors and their ligands in GC are not well established. Methods: We evaluated the expression levels of various ERBB receptor ligands (i.e., heparin-binding epidermal growth factor-like g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Another important molecule for EGFR signaling with an prognostic impact is its ligand AREG (39). Overexpression of AREG has been linked to therapeutic resistance (40).…”
Section: Discussionmentioning
confidence: 99%
“…Another important molecule for EGFR signaling with an prognostic impact is its ligand AREG (39). Overexpression of AREG has been linked to therapeutic resistance (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinicopathologic implications of other ligands, including HBEGF, TGF, betacellulin, and EGF, are insufficiently investigated. For HBEGF, a pivotal role in cancer progression has been proposed in various cancers, including cervical, breast, and gastric cancers [ 20 - 23 ]. In CRC, Kawasaki et al [ 24 ] suggested that HBEGF has roles in CRC progression through the recruitment of intestinal myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…HB-EGF might promote tumor growth and EMT by IL-4-conditioned media from macrophages [282]. Besides HB-EGF, other ErbB ligands (transforming growth factor-α (TGF-α) and amphiregulin (AREG)) have a prognostic impact on gastric cancer and might make up potential targets in cancer therapy [283][284][285]. Furthermore, trastuzumab sensitivity in gastric cancer can be predicted by HB-EGF expression [286].…”
Section: Heparin-binding Epidermal Growth Factor and Matrix Metalloprmentioning
confidence: 99%